Vitamin C: Overview of drugs and dietary supplements and analytical methods for determining its content - Sylwester Krukowski; Jakub Biały; Aleksandra Adamczyk; Aleksandra Kowalewska (Polskie Towarzystwo Farmaceutyczne, 2024)
Vitamin C is one of the most well-known and most frequently used substances found in various pharmaceutical preparations. Patients consider it as a safe compound with multidirectional beneficial effects, while chemists have been presenting various possibilities for its determination for many years. The aim of this review is to present the current range of drugs and dietary supplements containing vitamin C available in Poland, divided into appropriate categories, taking into account doses, forms and other ingredients. The second goal is to summarize the main analytical methods for determining the content of ascorbic acid. A review of available preparations showed disproportions between a small group of drugs and a very large group of dietary supplements, which turned out to be significantly diversified in various aspects. In turn, the review of analytical methods clearly indicates the dominant share of spectroscopic ones and the fact that researchers focus primarily on improving basic, commonly known techniques.